Socioeconomic profile of agroextractivists in associativism, Marajó archipelago, Pará, Brazil (Research, Society and Development, 2020)
The aim of the present study was to evaluate the socioeconomic profile of agroextractivists who practice associations in the archipelago of Marajó, state of Pará, Brazil. The study was carried out in the municipality of Breves, at the Ilha Pracaxi Settlement Residents Association (AMIP), with seven producers, in June 2019. Quanti-qualitative research was used, through the application of forms, with open and closed questions. Statistical analyzes were performed using the SPSS for Windows program, version 11.5. It was observed that there is a predominance of females in the total of associates. This population has an age range between 31 to 40 years, where 71.43% have some type of marital bond. Most (57.14%) have incomplete primary education. It was detected that 85.71% have housing with wooden structure. We emphasize that the main source of income comes from family farming. In addition to agricultural practice, respondents develop fishing and extractivism in the forest (57.14%). It is also worth mentioning that a part of the producers is granted social benefits, reaching an income of up to 2 minimum wages (42.86%). Due to the scarcity of data in the literature, this study carried out a cross-sectional analysis regarding the reality of associations in the Marajó archipelago. Thus, the provision of these data can assist in directing public policies that favor sustainable development in the region.